A Reliable Nd:YAG Laser Welded Stainless Steel 304 for Photonics Device Packaging Application - I.N. Nawi; None Saktioto; M. Fadhali; M.S. Hussain; J. Ali; P.P. Yupapin (My University, 2011)
An ultra compact pulsed Nd:YAG laser with laser beam peak power of 3.5 kW and 6.5 ms pulse duration is employed to produce a butt joint and lap joint for both spot and seam welding on a stainless steel 304 specimen. The strength test of the weld joints is conducted by pulling the joint materials using INSTRON Series IX/s Automated Materials Tester System. From the experimental results, it is found that a butt joint produces much stronger attachment than a lap joint. The stronger attachment is contributed by a larger volume of welded stainless steel 304 at the joint interfaces. However, the strength of a lap joint can be increased by producing a deeper weld penetration depth. It is done by controlling the laser beam parameters such as laser peak power and pulse duration. It is inferred that the commercial welding material, InvarTM, provides more robust joint than stainless steel 304. It is also concluded that the welded stainless steel 304 cannot attain the strength and elastic modulus of the stainless steel 304 itself. However, the stainless steel 304 is a good welding material for photonics device packaging by using pulsed Nd:YAG laser welding technique.
Keywords: Nd:YAG laser; Advanced optical system design